Ecomasjid: Kontribusi Pengurus Masjid dalam Membangun Masyarakat Berkelanjutan melalui Pengelolaan Lingkungan - Irfan, Irfan; Firdaus, Ade Rahman; Maharani, Yulia; Akbarudin, Suryamin (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study explores the contribution of the Masjid Raya Bintaro Jaya (MRBJ) management in building a sustainable community through the implementation of the Ecomasjid concept. Using a qualitative phenomenological approach, the study employed in-depth interviews, observations, and document analysis. Programs such as the Waste Charity Movement (Gerakan Sedekah Sampah), the #BringYourTumbler campaign, and the installation of solar panels have significantly impacted public awareness and reduced environmental footprints. The findings indicate that the mosque management successfully integrated Islamic values into sustainability practices by utilizing the mosque as a center for environmental education. Collaboration with external stakeholders supported the successful implementation of these programs. The study concludes that Ecomasjid can serve as a strategic model for other mosques to enhance community awareness and participation in environmental conservation. These findings highlight the potential of mosques as centers of social change based on religious teachings in addressing global environmental challenges.